2009
DOI: 10.1111/j.1742-7843.2009.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

The Hypoalgesic Effect of Oxycodone in Human Experimental Pain Models in Relation to the CYP2D6 Oxidation Polymorphism

Abstract: Oxycodone is O-demethylated by CYP2D6 to oxymorphone which is a potent μ -receptor agonist. The CYP2D6 oxidation polymorphism divides the Caucasian population in two phenotypes: Approximately 8% with no enzyme activity, poor metabolizers (PM) and the remainder with preserved CYP2D6 activity, extensive metabolizers (EM). The objective of the study was to determine if the analgesic effect of oxycodone in human experimental pain depends on its metabolism to oxymorphone. The analgesic effect of oxycodone was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 32 publications
6
70
3
1
Order By: Relevance
“…Thus, the third cohort was dosed to study the effect of PF-05105679 on the cold pressor test at 600 and 900 mg. From the pharmacokinetic analysis of the 300 mg, this maximum plasma concentration for this dose would be observed at the second cold pressor test evaluation with the 900-mg dose, and thus, was not tested in the efficacy arm of the study. PF-05105679 provided similar efficacy to the active comparator oxycodone (20 mg), the effects of which were consistent with previous studies with this opioid (Zwisler et al, 2009;Eisenberg et al, 2010). The differing time course of analgesia for both drugs is consistent with their pharmacokinetic profile.…”
Section: Trpm8 Antagonism Reduces Experimental Cold Pain In Humanssupporting
confidence: 78%
“…Thus, the third cohort was dosed to study the effect of PF-05105679 on the cold pressor test at 600 and 900 mg. From the pharmacokinetic analysis of the 300 mg, this maximum plasma concentration for this dose would be observed at the second cold pressor test evaluation with the 900-mg dose, and thus, was not tested in the efficacy arm of the study. PF-05105679 provided similar efficacy to the active comparator oxycodone (20 mg), the effects of which were consistent with previous studies with this opioid (Zwisler et al, 2009;Eisenberg et al, 2010). The differing time course of analgesia for both drugs is consistent with their pharmacokinetic profile.…”
Section: Trpm8 Antagonism Reduces Experimental Cold Pain In Humanssupporting
confidence: 78%
“…Different opioids have been applied in studies using the cold pressor test and have been found to be effective. The model was even sensitive enough to separate the effects of different genotypes in the subjects (Eckhardt et al, 2000;Grach et al, 2004;Zwisler et al, 2009Zwisler et al, , 2010Samer et al, 2010). Fentanyl has been tested in the cold pressor test, and this model was sensitive to the analgesia induced.…”
Section: Pharmacology Of Human Pain Modelsmentioning
confidence: 99%
“…Further oxidation of these metabolites via CYP2D6 (and CYP3A4) yields noroxymorphone [5,6]. Although the metabolites possess μ-opioid receptor activity, the relative contribution of the different metabolites to the central opioid effects are still to discussion [6,7].…”
Section: Introductionmentioning
confidence: 99%